Maternal and infant factors had a significant impact on birthweight and longitudinal growth in a South African birth cohort. (4th September 2017) - Budree, S; Stein, DJ; Brittain, K; Goddard, E; Koen, N; Barnett, W; Myer, L; Zar, HJ
Abstract: Aim: This birth cohort study investigated longitudinal infant growth and associated factors in a multiethnic population living in a low‐resource district surrounding the town of Paarl in South Africa. Methods: Between March 2012 and October 2014, all mothers attending their second trimester antenatal visit at Paarl Hospital were approached for enrolment. Mother–infant pairs were followed from birth until 12 months of age. Comprehensive socio‐demographic, nutritional and psychosocial data were collected at birth, two, six and 12 months. Infant anthropometry was analysed as z‐scores for weight and height. Linear regression was used to investigate predictors of birthweight, and linear mixed‐effects models were used to investigate predictors of infant growth. Results: Longitudinal anthropometric data from 792 infants were included: 53% were Black African, 47% were mixed race, and 15% were born preterm. Stunting occurred in 13% of infants at 12 months. Maternal height, antenatal alcohol and tobacco use, ethnicity and socioeconomic status were significant predictors of birthweight. In the adjusted mixed‐effects model, birthweight was a significant predictor of growth during the first year of life. Conclusion: Birthweight was an important predictor of growth trajectory during infancy. Birthweight and growth were influenced by several important modifiable factors.